Impact of air quality on enterprise productivity: Evidence from Chinese listed companies - Liu, Su; Yang, Yuetao; Cai, Ling (Frontiers in Environmental Science, 2023)
We provide insights and innovative ideas for China to achieve green development and promote high-quality economic development by studying the impact of air quality on enterprise productivity. This paper uses data from 2008 to 2016 for A-share companies listed on the Shanghai and Shenzhen stock markets, as well as the levels of particulate matter under 2.5 μm in diameter for 214 major Chinese cities. At the same time, this paper innovatively applies regression discontinuity and the Spatial Durbin Model for empirical testing. Considering the endogeneity, we choose the air flow index as an instrumental variable and the generalized space two-stage least squares method for the endogenous test. Additionally, we use dynamic regression and different spatial weight matrix to conduct robustness tests and reselect data from 2008 to 2012 and 2013 to 2016 as samples. Moreover, we test corporate heterogeneity from three perspectives: pollutant type, firm equity, and an industry’s technological level. The results show that the deterioration of local air quality significantly inhibits firm productivity, while the spatial spillover effects of pollution from surrounding cities also have a significant dampening effect on firm productivity. This negative effect is transmitted through research and development innovation capacity, human capital, and government subsidies. This empirical evidence from listed companies can be used for evaluating air quality management to enhance enterprise productivity, as well as to provide policy recommendations for boosting firm productivity through improved air quality.